Coccolith counting and reconstructed primary productivity results of core MD00-2354 - Zhou, Xinquan; Duchamp-Alphonse, Stéphanie; Kageyama, Masa; Bassinot, Franck; Doressoundiram, Florian; Kissel, Catherine (PANGAEA, 2022)
Coccolith assemblages of core MD00-2354 are used for reconstructing primary productivity in the northwestern Arabian Sea. The results cover the last 23,000 years. The attached data are original coccolith counting by using a polarized light microscope, and primary productivity. Counting result of each coccolith species is shown by the sum of counting number (n) in all fields of view. Primary productivity (gC m^-2 yr^-2) is calculated by an empirical equation that convert the percentage of lower euphotic zone species Florisphaera profunda to primary productivity. Details can be found in the related article.
Keywords: coccolith; Last Glacial Maximum; northwestern Arabian Sea; primary productivity